2018
DOI: 10.4049/jimmunol.1701618
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Induced T Cell Immunoparalysis: The Ins and Outs of Impaired T Cell Immunity

Abstract: Sepsis results in a deluge of pro- and anti-inflammatory cytokines, leading to lymphopenia and chronic immunoparalysis. Sepsis-induced long-lasting immunoparalysis is defined, in part, by impaired CD4 and CD8 αβ T cell responses in the postseptic environment. The dysfunction in T cell immunity affects naive, effector, and memory T cells and is not restricted to classical αβ T cells. Although sepsis-induced severe and transient lymphopenia is a contributory factor to diminished T cell immunity, T cell–intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(46 citation statements)
references
References 145 publications
(155 reference statements)
1
45
0
Order By: Relevance
“…1,3,12,13 A human acute monocytic leukemic cell line (THP-1 cell) is differentiated by PMA into macrophages and a lymphoblast cell line (Jurkat cell) was used as a model to study the crucial role of T lymphocytes. 4,5 Therefore, this study was conducted using THP-1 cells and Jurkat cells. This study is meaningful not only to confirm the action of PTX in macrophages and T lymphocytes but also to investigate the effects of PTX on T lymphocytes with hyper-inflammatory macrophages using co-culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,12,13 A human acute monocytic leukemic cell line (THP-1 cell) is differentiated by PMA into macrophages and a lymphoblast cell line (Jurkat cell) was used as a model to study the crucial role of T lymphocytes. 4,5 Therefore, this study was conducted using THP-1 cells and Jurkat cells. This study is meaningful not only to confirm the action of PTX in macrophages and T lymphocytes but also to investigate the effects of PTX on T lymphocytes with hyper-inflammatory macrophages using co-culture.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4 is expressed on the surface of monocytes and macrophages by LPS and activates NF-κB and ERK/MAPK pathways to secrete cytokines like TNFα, IL-1β, IL-6, IL-10, etc. [3][4][5]14 Migration inhibitory factor is secreted into the bloodstream during the process in which TLR recognizes bacteria or immune complexes to produce NF-κB, which in turn activates CD44/CD74 on the cell surface, thereby upregulating the expression of TLR on the cell surface and activation of NF-kB in the cell. 7,8 Also, MIF inhibits p53-mediated apoptosis, promotes cell proliferation, and overrides the anti-inflammatory effects of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis significantly reduces the number of lymphocytes ( 127 130 ), including CD8 T cells, via apoptosis ( 131 133 ). While naive (T N ) CD8 T cells are more susceptible to radiation-induced apoptosis and are lost to a greater extent than T CIRCM cells ( 134 ), both T N and T CIRCM cells display similar susceptibility to the sepsis-induced numerical decline ( 135 137 ). Additionally, further investigation into the subset composition of T CIRCM cells before and after sepsis reveals the numerical decline of T CM is equal to that of CD62L - T EM cells.…”
Section: Short- and Long-term Impact Of Sepsis On The Composition Of ...mentioning
confidence: 99%
“…4 However, specific guidelines are still lacking in the judgment of the therapeutic effect and prognosis of the disease, and how to judge the severity and prognosis of the disease is extremely important in clinical work. Studies have concluded that 5 that the level of lymphocyte subsets in peripheral blood of patients with sepsis is closely related to their prognosis. PCT has high clinical application value in sepsis, and can be used as a reliable indicator for the diagnosis of sepsis.…”
Section: Introductionmentioning
confidence: 99%